Fiber Optic Tire Speed Sensor - Gubaidullin, R. R.; Agliullin, T. A.; Sahabutdinov, A. Zh (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
This article presents the results of modeling and comparative analysis of the real-time efficiency of the microwave photonic measurement system for assessing the angular velocity of a vehicle tire for two types of addressed fiber Bragg structures. The relevance of this research is due to the development of active vehicle safety and fiber-optic measuring devices. Since knowledge of the change in adhesion properties of the tire is the most important information for the active vehicle safety systems. This fact is forcing engineers to create measuring devices capable of measuring at a high sampling rate, which can be achieved using the technology of polling addressed fiber Bragg structures.